INTERACTION OF OXYGEN WITH CHROMIUM(III) OXIDE - CHEMISORPTION STUDIES AND THE EFFECTS OF SURFACE ADDITIVES - Foord, J; Lambert, R (1986)
The interaction of oxygen with the epitaxially grown Cr2O3(0001) oxide surface has been examined using LEED, TDS, XPS and Δφ measurements. Oxygen adsorbs into two binding states on the outgassed oxide surface, with associated heats of adsorption of 110 and 210 kJ mol-1. Isotope scrambling measurements reveal that the more weakly adsorbed (α) oxygen is molecular in nature, whereas dissociation occurs within the strongly bound (β) state. Oxygen exchange between the oxide lattice and the gas phase also takes place via the β state and the nature of this process is discussed. The effects of the surface additives, Na and Cl, on oxygen adsorption have been investigated. The presence of Na stabilises formation of Cr(VI) species at the oxide surface, whereas Cl selectively blocks ß-oxygen formation. © 1986.